Pembelajaran Kontekstual berbasis KBDLS untuk Meningkatkan Literasi Siswa SD - Bustari Bustari; Martin Kustati; Rizki Amelia (ANWARUL, 2025)
The limited number of studies on school-based contextual learning serves as the background for this research, despite its significant impact on the development of literacy among elementary school students. This study aims to analyze the implementation of the Learning Activities Outside the School Environment Program (Kegiatan Belajar di Luar Lingkungan Sekolah, KBDLS) and describe its effects on improving student literacy. A descriptive qualitative method was employed, with research subjects including the principal, classroom teachers, supporting teachers, and selected students, identified through purposive sampling. The findings reveal that the implementation of the KBDLS Program enhances learning motivation, writing skills, critical thinking abilities, and students’ capacity to connect observational experiences with academic content. These results support the theories of Contextual Teaching and Learning (CTL) and experiential learning, reinforcing the argument that real-world and environment-based learning promotes holistic literacy development. The study concludes by highlighting the crucial role of teachers as facilitators in optimizing the learning potential of the environment. The implications include theoretical contributions to the literature on contextual learning and literacy, as well as practical recommendations for elementary schools to replicate the KBDLS model as a strategy for improving students' literacy quality.